Step aside, millennials and centennials! The attitudes of baby boomers toward social media influencers - Levi, E.; Ozcelik, A.B. (Nova Science Publishers, Inc., 2021)
Since digital tools are thought to be used mostly by young people, influencer marketing is assumed to appeal to Generations Y and Z. However, the online behaviours of Baby Boomers have changed as use of social media has become widespread. This study investigates the attitudes of Baby Boomers toward social media influencers. Using an exploratory research design, in-depth-interviews are conducted to discover the attitudes of Baby Boomers towards influencers and, more specifically, provide insights into (1) how much Baby Boomers know influencers, (2) how much they rely on the suggestions of influencers, (3) which factors make them more likely to rely on those suggestions, and (4) whether they make (or intend to make) purchases in accordance with those suggestions. The findings reveal that, contrary to popular belief, Baby Boomers may hold positive attitudes toward social media influencers; they do not exclude influencers categorically, but rather contextualize their judgments depending on the qualities of the influencer in question. Specifically, they expect expertise, experience, authenticity, and similarity to trust an influencer. This study is among the first to examine how Baby Boomers, supposedly traditional consumers, relate to one of the newest marketing strategies. The results provide a preliminary foundation for researchers in this field and valuable consumer insights for marketing professionals. © 2021 Nova Science Publishers, Inc.
Keywords: Baby Boomers; Digital Marketing; Generations; Influencer Marketing; Social Media İnfluencers